(untitled) (Modern education and development, 2025)
This article discusses the role of information technologies in the process of teaching foreign languages ​​and their impact on educational effectiveness. Information technologies, in particular, allow for the improvement of teaching methods through computer programs, online platforms, video lessons, interactive tests and virtual learning environments. Research shows that these tools increase students’ interest in knowledge, make the lesson process more interesting and effective, and create favorable conditions for language learning. This article analyzes the practical importance, advantages and ways of their effective introduction into education.